Subjective wellbeing, sense of humor and psychological health in hemodialysis patients - Luis Manuel Mota Sousa; Ana Vanessa Antunes; Cristina Maria Alves Marques-Vieira; Paulo César Lopes Silva; Olga Maria Martins de SousaValentim; Helena Maria Guerreiro José (Sociedad Española de Enfermería Nefrológica, 2019)
Objective: To investigate the relationship between satisfaction with life in general, sense of humor, and anxiety, depression and stress with subjective happiness in chronic kidney disease patients undergoing hemodialysis. Material and Methods: A cross-sectional and correlational study was developed in two units of the Diaverum dialysis clinic and one hospital unit, with 183 chronic kidney disease patients undergoing hemodialysis. An instrument was used to characterize the sociodemographic and clinical profile of the sample (age, gender, nationality, education, occupation, marital status, dialysis sessions length, presence of hypertension and diabetes): the subjective happiness scale; the satisfaction with life in general; depression, anxiety and stress scale 21; and multidimensional sense of humor scale. Inferential procedures included Spearman correlation coefficients, and multiple linear regression adjusting to age, marital status, professional activity and diabetes. Results: Subjective Happiness was positively correlated with satisfaction with life in general, and the three dimensions of Sense of Humor. Nevertheless, subjective happiness was negatively correlated with stress / anxiety and depression. Satisfaction with life in general, humor production and social use of humor, and attitude towards humor had a positive relationship with subjective happiness. However, depression had a negative relationship with subjective happiness. Conclusions: Higher levels of subjective happiness were associated with higher levels of satisfaction with life in general, and sense of humor, however they were also associated with lower levels of depression in patients undergoing hemodialysis.